A double end fault location technique for distribution systems based on fault-generated transients - Aboshady, F.M.; Sumner, Mark; Thomas, David W.P. (2017)
This paper presents a fault location technique for distribution systems. It is a two end impedance based technique that uses the fault generated transients to estimate the fault distance over a broad range of frequencies. Then, curve fitting is applied to find the final estimated fault distance. Firstly, the paper introduces the method for the system represented as a lumped RL model. Then, generalized to consider the distribution line capacitance. The technique accounts for presence of loading taps, heterogeneous feeder sections, single phase, two phase and three phase loads and unbalance in distribution system. Single line to ground, line to line, and three phase faults are considered at different fault resistance values up to 100 Ω. Also, the effect of fault inception angle and resolution of analogue to digital converter is investigated. IEEE 34 nodes system is used to evaluate the proposed method.